Rehabilitating the role of active management for pension funds - Aglietta, Michel; Brière, Marie; Rigot, Sandra; Signori, Ombretta (Journal of Banking & Finance, 2012)
Pension fund returns can be decomposed into different sources, including market movements, asset allocation policy, and active portfolio management. We use a unique database covering the asset allocations of US defined-benefit pension funds for the period 1990–2008, and we test the role of each factor in explaining their returns. Our results shed new light on pension funds’ sources of performance. While the previous literature emphasized that policy allocation accounts for the bulk of returns, leaving little room for active management, we show that taking explicit account of market movement can change the results significantly. Although active management plays a minor role in global asset allocation, its role is predominant in explaining returns to individual asset classes, whether traditional or alternative. This paper rehabilitates the contribution of active management as a source of performance for pension funds, at least at the asset class level.